Processo de projeto colaborativo em arquitetura - Edler Oliveira Santos (2014)
This work is part of the field on designs practice research, and it aims to understand what sets a collaborative experience in the design process, their specificities and from which context it comes from. The statement, which says that, in practice, the activity of making projects depends on the interaction between several actors, mainly architects, clients and users is the bottom line for the research about how the relationship between those can lead the buildings creative process. In order to accomplish this goal, two case studies were realized at two architectural offices that works on the projects market in the city of Belo Horizonte/Mg, which were monitored while they were developing architectural projects. Those offices practices, linked to theoretical referential about the present theme, were able to raise discussions about those aspects which influence the team project activity, such as monopoly and sharing of tasks and decisions, exchange of ideas and negotiation of solutions. The achievements indicate that collaboration is structured upon needs and contingency and, like this, it can be a condition to the projects.